The reluctant fundamentalist - Hamid, Mohsin, 1971- (2008)
Changez, a young Muslim American, is living the American dream, with a Princeton education and high-paying job, until the events of September 11th force him to confront his personal allegiances.
Includes discussion guide.
Keywords: Pakistani Americans -- Fiction; Race discrimination -- Fiction; Self-perception -- Fiction; Fiction; Fiction